Pengetahuan dan Perilaku Merokok pada Pasien Hipertensi (Journal of Telenursing (JOTING), 2024)
This study aims to examine the relationship between the level of knowledge and smoking behavior in hypertensive patients at the Bandar Lampung Adventist Hospital. This research is a simple descriptive quantitative research. The results of the study showed that the relationship between knowledge and smoking behavior in hypertensive patients at Bandar Lampung Adventist Hospital had a significance value of 0.047 (p